The establishment process of Türk traktör between 1948 and 1963: a critique of ‘modernization’ as development in Early Cold War Turkey - AYKAÇ, GÜLŞAH (My University, 2023)
Beginning with the Marshall Plan, the political and economic strategies of the United States shaped Turkey’s modernization desires. Modernization was reflected in various urban and spatial applications, such as the building of new factories, dams, and highways constructed with American capital and service. Turkey’s first tractor factory, established in 1954 with an American partner, Minneapolis-Moline, offers productive grounds for research that addresses modernization discourses on the ‘Western’ development models of the period. The tractor factory was opened in the building of a formerly aircraft engine factory in Atatürk Forest Farm representing modernization programme of the young Republic. This change from production of aircraft engines to the production of tractors represents a shift in the modernization paradigm from early Republican period to the Cold War Turkey. The establishment process of a tractor factory was in line with technological developments in agriculture, which had a role in urbanization in accordance with both industrialization and reduction of the rural workforce in developed Western countries such as the US. However, this multidisciplinary study highlights the rural and urbanization contradictions of Turkey and the dynamics of the period regarding the dilemma of modernization as development.
Keywords: Mimarlık; Şehir ve Bölge Planlama; Kent Planlaması ve Gelişimi; Mimarlık Tarihi ve Restorasyon; Mimarlık Tarihi; Mühendislik ve Teknoloji; Architecture; City and Regional Planning; Urban Planning and Development; History of Architecture and Restoration; History of Architecture; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; MİMARİ; Engineering, Computing & Technology (ENG); Arts & Humanities (AHCI); ARTS & HUMANITIES; ARCHITECTURE; Mimari; Fizik Bilimleri; Physical Sciences